ANALISIS KETERKAITAN INSTRUMEN KEBIJAKAN MONETER, DEFISIT ANGGARAN, DAN NERACA PEMBAYARAN INDONESIA TAHUN 2002 - 2017 - Jeremy, Orlandio (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2019)
This study aims to analye the linkages of monetary policy instruments, budget deficit and balance of payments with VECM method. This study used secondary data from 2002 quarter I to 2017 quarter IV.            The result found one-way interaction between open market operation with Indonesian balance of payments. Money supply has two-way causality relationship with budget deficits and minimum reserve requirement. The exogenous variable which are BI rate and open market operation affected Indonesian’s balance of payments with  positive correlation, while the minimum reserve requierment significantly affect Indonesian’s balance of payments with negative correlation. Impulse response found shock of money supply respond to balance of payments positive in the fourth period.This result show that Indonesia’s balance of payments is a monetary phenomenon. So monetary policy instruments BI rate, minimum reserve requirement and open market operation can be used to maintain the stability of Indonesia’s balance of payment.